Prioritization of production strategies of a manufacturing plant by using an integrated intuitionistic fuzzy AHP & TOPSIS approach - Karasan, Ali; Erdogan, Melike; Ilbahar, Esra (EMERALD GROUP PUBLISHING LTD, 2018)
Purpose The purpose of this paper is to find most appropriate production strategy for a manufacturing plant by using an integrated interval-valued intuitionistic fuzzy (IVIF) analytic hierarchy process (AHP) and technique for order preference by similarity to ideal solution (TOPSIS) approach. Design/methodology/approach The applied methodology is a multi-criteria decision making approach consists of AHP and TOPSIS methods with the extension of intuitionistic fuzzy sets. Findings Results of the application are revealed that using integrated IVIF-AHP & TOPSIS methods are very appropriate for the prioritization of the strategy for the production management for a manufacturing plant. This outcome also is supported by the sensitivity analysis. Results of the sensitivity analysis demonstrate the robustness of the methodology. Originality/value To the best of the authors' knowledge, an integrated IVIF-AHP & TOPSIS methodology is used for the prioritization of production strategies for the first time.
Keywords: AHP; MCDM; TOPSIS; Intuitionistic fuzzy sets; Production strategies; MULTICRITERIA DECISION-MAKING; GREEN PRODUCTION STRATEGIES; COMPETITIVE PRIORITIES; OPERATIONS STRATEGY; TAXONOMY; PERFORMANCE; CONFIGURATIONS; ENVIRONMENT; Computer Science; Information Science & Library Science; Business & Economics